2021
DOI: 10.1177/1938640021993630
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation Rates Following Total Ankle Arthroplasty Versus Ankle Arthrodesis for Posttraumatic Indications

Abstract: Aims: This studied aimed to compare rates of reoperation for patients who received primary ankle arthrodesis (AA) versus total ankle replacement (TAR) for posttraumatic indications between 2010 and 2016 Q2 using a nationwide claims database. Methods: A retrospective cohort study analyzing patients who received primary AA or TAR for posttraumatic indications was performed using PearlDiver. Reoperations assessed included prosthetic joint infection (PJI), hardware removal, adjacent joint fusion, and local open re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Despite the abundant literature showing several advantages of TAA compared to ankle arthrodesis, [1][2][3]28,30,31,34 ideal surgical options for younger age patients remains an important topic of debate when considering TAA. Several studies have shown similar outcomes and survivorship among younger patients and elderly after TAA.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the abundant literature showing several advantages of TAA compared to ankle arthrodesis, [1][2][3]28,30,31,34 ideal surgical options for younger age patients remains an important topic of debate when considering TAA. Several studies have shown similar outcomes and survivorship among younger patients and elderly after TAA.…”
Section: Introductionmentioning
confidence: 99%